Avoiding a Panglossian Policy Science: The Need to Deal with the Darkside of Policy-Maker and Policy-Taker Behaviour. (4th May 2022) - Howlett, Michael
Abstract: Current work on policy design typically views policy-making as an activity on the part of well-intentioned governments desiring to serve the public interest by marshaling accurate evidence in a dispassionate, technical way in the attempt to address and resolve public problems. Even those studies which do note the political and power-based nature of many aspects and instances of policy-making still hold out hope that these "distortions" can be corrected and effective policy solutions emerge from policy deliberations. While this optimism is laudable, such thinking does a disservice to policy design and policy studies by failing to address head-on the possibilities, often observed in policy-making practice, that policy-makers may be driven by malicious or venal motivations rather than socially beneficial or disinterested ones and that policy targets also have proclivities and tendencies towards activities such as gaming, free-ridership and rent-seeking that must be curbed if even well-intentioned policies are to achieve their aims. This paper addresses both these issues and the state of the policy design literature on the causes, consequences and correctives for such behaviour. It proposes a new research agenda dealing with this "dark side" of policy behaviour and the manner in which policy designs can include procedural policy tools in order to deal with these problems.